Implementasi Pendidikan Kewarganegaraan dalam Pembentukan Karakter Demokratis Pemuda: Perspektif Wagub Dimyati tentang Baris-Berbaris sebagai Upaya Melawan Apatisme - Indah Dwi Sutarini; Nurlya Fitri Salsabila; Yufita Tarru Hegi; Sulistiawati (Staatsrecht: Jurnal Hukum Kenegaraan dan Politik Islam, 2025)
This study aims to analyze the implementation of Civic Education in shaping the democratic character of youth through the perspective of the Deputy Governor of Banten, A. Dimyati Natakusumah, regarding marching activities as an effort to counter apathy. The declining levels of discipline, accuracy, solidarity, and nationalism among students highlight the urgent need for continuous character development. Using a qualitative approach through content analysis of the Deputy Governor’s statements, this study finds that marching activities contain core Civic Education values such as discipline, cooperation, responsibility, mutual assistance, and patriotism. These activities not only train physical coordination but also cultivate democratic character through social interaction, strengthened civic engagement, and the habituation of positive behavior. The findings emphasize that marching serves as an effective, simple, and applicable method for enhancing youth character while reducing apathy. This research contributes to the development of contextual character education models within school environments.